Supply chain of innovation and new product development. Issue 4 (December 2015) - Mazzola, Erica; Bruccoleri, Manfredi; Perrone, Giovanni
Abstract: This paper conceptualizes the supply chain of innovation of a company as its supply chain not related to physical goods exchanges but to R&D commodities exchanges. R&D commodities, being the outcomes of research activities, are for example patents, technologies, research services, studies, projects, etc. Specifically, we focus on the relationship between the activities of purchasing/selling R&D commodities and the propensity of the firm to develop new products; we examine how the position of the firm within its innovation network moderates this relationship. The empirical setting of the research consists of a cross-sectional dataset of 544 biopharmaceutical companies that have signed 1772 R&D agreements in the years 2006–2010. We find firstly, evidence of the supply chain of innovation (as a natural evolution of the well-acknowledged dual-market model of the biopharmaceutical industry). Secondly, we find that the relational embeddedness, coming from innovation network, influences the effect of purchasing and selling R&D commodities on new product development. Supporting our theoretical predictions, this paper offers contributions to the scientific literature on supply chain relationships in new product development. Highlights: In this paper we conceptualize the supply chain of innovation (SCoI). We compare the supply chain of innovation and the supply chain of materials. We focus on the relationship between purchasing/selling R&D and NPD. We study the role of relational embeddedness within the innovation network.